Los huertos familiares y su contribución a la seguridad alimentaria y la sostenibilidad económica de los habitantes del recinto “El Vergel”, cantón Valencia - Caliz Aldaz, María Esther (2018)
The present investigation entitled "Quantities of Valencia". It was carried out with the purpose of knowing the benefit of consuming food and medicinal plants, as well as knowing how this activity translates into the sustainability of the Families of the "El Vergel" Campus. The objective was stated: "El vergel", Cantón Valencia. The implicit study methods are inductive, inductive, analytical, descriptive, collected, information gathered through surveys and observations related to the objectives set out in the project. It is shown that 75% of the families in their garden have a maximum of two banana plants; since it is a daily food and its remnants what is used to generate income, to continue with the orange and the mango, the medicinal plants of greater presence, the aloe, the oreganite, the albaca and the ornamental plants; They are the roses, the plant known as the wand of justice and the bonds of love. We all cultivate in a very traditional way, in recycled materials such as: plastic bottles, baskets, tires, flowerpots, recycle seeds or seedlings. The irrigation system is the medium of hoses, tanks and, some families use organic fertilizers such as compost, earthworm humus and sowing soil. As for the lifestyle, it is seen that it is subsistence, that no family lives from the gardens, although it also serves as family support and is used to improve the economic sustainability of their homes, they do not have health insurance, which corresponds Most of the housing is owned, we all have electricity, very few have water through pipes and sewers. Keywords: Family gardens, production system, socio-economy, economic sustainability